LESSONS FROM A SECULAR STATE: ESSENCE OF THE CONSTITUTION AND ITS IMPLICATION ON JUDICIAL INTERPRETATION OF HUMAN RIGHTS PROVISIONS IN TURKEY AND MALAYSIA - Farid Sufian Shuaib; Murat Tumay, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2019)
Malaysia and Turkey, to a different degree and in different areas, continue to construct an Islamic identity. However, a clear divergence of position pertaining to religion can be seen in their respective constitutions, in particular with regard to the position of Islam and secularism. It is interesting to examine the constitutional position of religion and its consequence and influence in the construction of the constitution and legislation. The paper looks at the text of the constitutions and the approaches taken by the apex court in the two countries. The paper also looks at the jurisprudence of the European Court of Human Rights since Turkey is a signatory of the Convention for the Protection of Human Rights and Fundamental Freedoms. The opposing positions taken by the two constitutions with regard to the influence of religion in public affairs surprisingly offers a coherent approach in constitutional construction.